Effects of Prior Annealing on the Spark Plasma Sintering of Nanostructured Y2O3 Powders. Issue 5 (28th February 2015) - Attia, Mohamad A.A.; Orrù, Roberto; Delogu, Francesco; Montinaro, Selena; Garroni, Sebastiano; Ewais, Emad M.M.; Cao, Giacomo
Abstract : The effects produced by annealing Y2 O3 nanopowders on their spark plasma sintering (SPS) behavior are systematically investigated in this work. It is found that the annealed powders display higher sinterability with respect to the as‐received ones. Indeed, the maximum densification level reached from pristine powders is about 97.5%, whereas density decreases when further increasing either the sintering temperature or the dwell time. In contrast, the density of SPS products obtained from pretreated powder monotonically increases with temperature and processing time, thus leading to fully dense materials in 30 min at 1050°C and 60 MPa. Correspondingly, it is found that the annealing treatment markedly inhibits grain coarsening during SPS. Thus, dense translucent samples with grain size below 100 nm can be attained from annealed powders. On the other hand, white‐opaque specimens with significantly coarser microstructures (up to 1‐μm‐sized grains) are obtained when pristine powders are directly processed under the same sintering conditions. Furthermore, it is observed that the annealing treatment of SPS samples in air allows for graphite contamination removal, whereas no improvement in term of light transmittance is produced.